Projecto, património arquitectónico e regulamentação contemporânea. Sobre práticas de reabilitação no edificado corrente - Nuno Valentim Rodrigues Lopes (2016)
The present thesis is an approach to the uncommon reflection about project, architectural heritage and contemporary regulation. The analysis focuses on cases where intervention was operated on common buildings of the end of the 19th and the beginning of the 20th centuries, constructions with heritage value. In all cases, intervention is explicit (from restoration to more profound rehabilitation) and the preservation of identifiable architectural values is a concern. Simultaneously, all cases show incompatibilities with current regulatory and procedural framework. What should be the approach in such interventions and category of buildings? Confronted with such rich diversity of existent buildings, how should actions within a regulatory framework at the same time guarantee the capacity of adjusting to circumstance? If, on the one hand, there is an unprecedented interest in issues concerning rehabilitation (parallel to an increasing number of rehabilitation projects), on the other hand, interventions in non-listed buildings are subject to the general construction regime as applied to new buildings. The risk of ruining patrimonial values in such buildings in order to abide by the law is huge, making it urgent to address this issue, i.e. a reflection about practice, research and the development of knowledge in this particular area. The purpose is therefore to evince the inadequacies of current regulatory framework concerning interventions in common existent buildings in the referred timespan, hopefully leading to the required and urgent adjustments. The analysis of the selected case studies overlaps a precise observation of each existent building, the identification of architectural values, project decisions and the interpretation of the current regulatory and procedural framework - from actions concerning each intervention to the drawing up of an evaluation summary. This overview, applied as a matrix of incompatibilities, provides the intersection, the interpretation and the synthesis of the analysis, based on the studied cases, as a means for the sought critical judgment. Not only is this assessment a contribution to improve architectural practices, but it is as well an attempt do adjust regulatory principles which are enriched culturally, more coherent and efficient concerning common/typical buildings of patrimonial value.